2008
DOI: 10.1016/j.ydbio.2008.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally acquired PKA localisation in mouse oocytes and embryos

Abstract: Localisation of Protein Kinase A (PKA) by A-Kinase Anchoring Proteins (AKAPs) is known to coordinate localised signalling complexes that target cAMP-mediated signalling to specific cellular sub-domains. The cAMP PKA signalling pathway is implicated in both meiotic arrest and meiotic resumption, thus spatio-temporal changes in PKA localisation during development may determine the oocytes response to changes in cAMP. In this study we aim to establish whether changes in PKA localisation occur during oocyte and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Therefore, it is possible that cAMP is able to readily diffuse throughout the oocyte cytoplasm prior to LH stimulation to activate intracellular PKAs. In support of this, the catalytic subunit of PKA is present both in the plasma membrane and throughout the cytoplasm (Brown et al 2002, Webb et al 2008.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, it is possible that cAMP is able to readily diffuse throughout the oocyte cytoplasm prior to LH stimulation to activate intracellular PKAs. In support of this, the catalytic subunit of PKA is present both in the plasma membrane and throughout the cytoplasm (Brown et al 2002, Webb et al 2008.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, b 1 -ARs generate cAMP signals capable of diffusing over 10 mm throughout large adult ventricular cardiomyocytes even in the absence of PDE inhibitors (Nikolaev et al 2006). AKAPs have been identified in mouse oocytes (Brown et al 2002, Kovo et al 2006, Newhall et al 2006) and the RI-and RII-type PKAs are tethered in the plasma membrane and the cytoplasm respectively (Brown et al 2002, Newhall et al 2006, Webb et al 2008. However, PDE activity is kept low in oocytes by cGMP, which is produced in the Figure 6 Inhibiting endocytosis with dynasore increases cAMP levels in oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Optical indicators based on Förster resonance energy transfer (FRET) Russwurm et al, 2007;Willoughby and Cooper, 2008) are ideal for this purpose. These sensors have been used in mouse oocytes (Webb et al, 2002;Webb et al, 2008), although not in oocytes within antral follicles. The sensor used in those studies, comprising fluorescent catalytic and regulatory subunits of PKA, has the disadvantage of inhibiting meiotic progression (Webb et al, 2002), probably because it elevates PKA activity (Goaillard et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the Akinase anchoring proteins (AKAP), which contain a targeting domain for specific subcellular localizations, translocate PKA to some intracellular compartments by binding to PKA-Rs. There are more than 40 members in the AKAP family [30], and it has been reported that at least AKAP1, AKAP2, and AKAP7c are expressed in mouse oocytes [15,31,32]. Among these AKAPs, AKAP1 has been reported to be essential for meiotic maturation involved in the translocation of PKA-R2 to the mitochondria [15].…”
Section: Discussionmentioning
confidence: 99%